Investigating Fluency and Accuracy of Japanese University EFL Learners’ Spoken English Production - Tokunaga, Miki (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2021)
Japanese learners of English are often described as having good English grammar but lacking in fluency. However, with the changes to a more communication-focused English curriculum in the last few decades, this is no longer the norm. This paper will first review the reactions to communication-focused English instructions in Japan and other parts of Asia, then discuss the current study which explored the grammatical accuracy and fluency of spoken English production of 45 Japanese university EFL learners who had studied under the communication-focused curriculum in junior and senior high schools. The results of the study showed that, as a group, the participants were neither accurate nor fluent. Although some participants were able to produce sentences accurately using easier grammar structures, their production was very slow, indicating the retrieval of declarative knowledge instead of proceduralized knowledge. Literature review and the results of this current study suggest that the communication-focused curriculum has not been successful in developing fluency among Japanese English learners, and that their accuracy has suffered from decreased amount of grammar instructions. Instead of switching the focus from grammar to communication, balanced grammar instruction and fluency practice are needed.